2015
DOI: 10.1038/srep11614
|View full text |Cite|
|
Sign up to set email alerts
|

Flotillin-2 promotes metastasis of nasopharyngeal carcinoma by activating NF-κB and PI3K/Akt3 signaling pathways

Abstract: Lipid raft proteins have been confirmed to be important in cell signal transduction. Some reports have shown that the aberrant expression of lipid raft proteins is associated with malignant phenotypes in some cancers. However, the role of the lipid raft protein flotillin-2 (Flot-2) in nasopharyngeal carcinoma (NPC) remains to be comprehensively characterized. Here, overexpression of Flot-2 in NPC tissues and cell lines was detected by immunostaining, and Flot-2 expression was found to be positively associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
59
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 53 publications
6
59
0
Order By: Relevance
“…A co-localization of PI(4,5)P 2 and flotillins was also observed in pathological neuronal structures typical for the brains of Alzheimer's disease patients, suggesting their common involvement in neurodegeneration [136]. Flotillins have also been indicated as regulators of the PI3-kinase/AKT pathway crucial for cancer cell survival [137,138]. PI(4,5)P 2 can be enriched in rafts, and a significant elevation of its level in rafts occurs during the LPS-induced clustering of CD14, a GPI-anchored plasma membrane raft protein assisting the TLR4 receptor of macrophages in pro-inflammatory signal transduction [99,139].…”
Section: Flotillins Affect Sphingosine-1-phosphate Signaling and Arementioning
confidence: 94%
“…A co-localization of PI(4,5)P 2 and flotillins was also observed in pathological neuronal structures typical for the brains of Alzheimer's disease patients, suggesting their common involvement in neurodegeneration [136]. Flotillins have also been indicated as regulators of the PI3-kinase/AKT pathway crucial for cancer cell survival [137,138]. PI(4,5)P 2 can be enriched in rafts, and a significant elevation of its level in rafts occurs during the LPS-induced clustering of CD14, a GPI-anchored plasma membrane raft protein assisting the TLR4 receptor of macrophages in pro-inflammatory signal transduction [99,139].…”
Section: Flotillins Affect Sphingosine-1-phosphate Signaling and Arementioning
confidence: 94%
“…AKT3 belongs to the AKT family and has three closely-related isoforms AKT1, AKT2, and AKT3 that presumably play similar roles in cell proliferation, survival, metabolism, and many other cellular functions [28]. Various studies have shown that AKT3 plays an important role in cell migration in cancer [29][30][31], but little is known about the role of AKT3 in retinopathy. The role of AKT3 in angiogenesis has been implicated in several studies.…”
Section: Discussionmentioning
confidence: 99%
“…SCLC has the pathological characteristics of high degree of malignancy, low degree of differentiation, rapid growth, invasion of blood vessels, early and extensive metastasis with poor biological behavior and dangerous prognosis. Moreover, SCLC patients are less symptomatic before diagnosis and survive shorter than patients with other types of lung cancer [4][5][6]. Although a number of studies have demonstrated that many molecular triggers play a vital role in the development of SCLC, the mechanisms underlying the process remain unclear.…”
Section: Introductionmentioning
confidence: 99%